The Role of Entrepreneurship as a Solution to Reducing Unemployment in East Java - Dwi Anggia Azzahra; Rahmah Salsabila Al Maghfuri (Rashid : Journal of Economic, 2026)
This study aims to analyze the role of entrepreneurship in reducing unemployment in East Java and to identify various efforts that can be undertaken to enhance entrepreneurial interest and capabilities among the community. The method used in this study is a literature review by examining scientific publications, statistical data, and previous research related to entrepreneurship and unemployment. The proposed solutions include improving entrepreneurship education and training, strengthening access to capital for Micro, Small, and Medium Enterprises (MSMEs), utilizing digital technology for business development, and providing government support through business incubation and mentoring programs. The findings indicate that the development of entrepreneurship contributes positively to employment creation and unemployment reduction in East Java. Furthermore, new entrepreneurs who are supported by adequate capital, skills, and technology have greater opportunities to grow and generate employment for surrounding communities.